Development of PC based router using Quagga - Rosnaiza Hasan (Universiti Malaysia Perlis, 2008)
Project entitled “Development of PC Based Router using Quagga” is aim to build a routing service that has high quality and be one of the routing solutions for the programmer. This project studied the routing process, which will move information from a source to a destination across an inter-network. The methodologies of this project are dividing into phases and step by step. The hardware required in this project is computers, two switches, and two network cards. The software that required are Linux operating system, and Quagga; the routing software packages. Finally, the product of this project is a router, which can move information from a source PC to a destination PC, in safe condition and can run efficiently.